PSYCHOSOCIAL INTERVENTION IN SEXUAL VIOLENCE AGAINST CHILDREN: REFLEXIVITY AND PSYCHODRAMATIC RESOURCE - Denise Lima Moreira; Liana Fortunato Costa (Revista Brasileira de Psicodrama, 2021)
This study aims to discuss the reflexivity of female children victims of sexual violence during a psychosocial intervention with a psychodramatic orientation, seeking out to understand the meanings present in the dialogues and plays. The research participants were 13 girls victims of sexual violence perpetrated by an adolescent close relative. Two group sessions records were used to focus on the interpretation of reflexivity on the theme of protection. The results describe the sessions in the organization: warm-up, dramatization and sharing. The discussion focuses on the earnings that play and dramatic plays bring to reflexivityabout a topic such as arduous as sexual violence. The creation of a playful environment favors a dialogue between victims and adolescent offenders.